A retrospective single-center study in 20 patients with midline nasal masses: which site has the highest risk of recurrence? - Yılmaz Topçuoğlu, Miray-Su; Plinkert, Peter K.; Seitz, Angelika; El Damaty, Ahmed; Bächli, Heidi; Baumann, Ingo (Annals of otology, rhinology & laryngology, 2025)
Objectives: Midline nasal masses are rare and challenging for surgeons. This study examined the site with the highest risk of recurrence following midline nasal mass excisions. - Methods: Surgical outcomes were retrospectively reviewed following excision of midline nasal masses between 2010 and 2022 in the predominantly pediatric patient cohort. The primary outcome measure was the recurrence rate. - Results: Overall, 22 nasal masses were resected from 20 patients. Of these masses, 16 were nasal dermoid sinus cysts (NDSC), 2 were hamartomas, 1 was an epidermoid cyst, and 1 was a mature teratoma. Five of the nasal masses were classified as intracranial lesions, 11 were classified as intraosseous lesions, and 6 were classified as superficial lesions. The open rhinoplasty approach was chosen in 65% of the surgeries. For the intracranially extended lesions, a combined nasocranial approach was performed. Four revision surgeries were performed due to superficial recurrences at the nasal dorsum of lesions, that were primarily classified as intraosseous lesions. - Conclusions: All recurrences had a superficial extension and were easily excised. Intraosseous NDSC have the highest risk of recurrence, but conversely, they also occur most frequently.